SPONTANEOUS SUFFERING, ART AND YOGA: THE BUDDHIST CONTEXT - Pandey, Krishna Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Lord Buddha said that all human beings on this earth are unhappy. He did not define sorrow, he only indicated it that when a human is born, he experiences sorrow, when old age surrounds him, he experiences sorrow, when he dies, he experiences sorrow, when he comes in contact with something unpleasant (person, thing, event etc.), he experiences sorrow, similarly separa-tion from a loved one also becomes the cause of sorrow. Thus, in every event of life, he saw the inevitable presence of the element of sorrow or Dharma and preached about it, but he did not clearly state what sorrow actually is, rather he pointed out the places, symptoms and character-istics indicating its presence and left its discovery to the efforts and endeavor of man. Man un-derstood that the unfavorable sensations are sorrow, and thus man found it as a Dharma rela-tive to or parallel to or competitive to the favorable sensations. Besides this, man also under-stood that the religion which is endured with difficulty, which is evil, is the religion of sorrow.